CML EKSA team levels up! - Siti Ainun Jariyah, Hassan; Rosnani, Ismail; Jamilah Bebe, Mohamad (UMPSA, 2025)
Pekan, 13 January 2025 – Several staff members from the Centre for Modern Languages (CML) attended the UMPSA Ekosistem Kondusif Sektor Awam (EKSA) Internal Auditor Workshop 2025 organised by the Centre for Strategic and Quality Management, UMPSA. The two-day workshop was held on 13-14 January at the Banquet Hall, UMPSA Pekan.